MENGENAL LEBIH DEKAT PERAN DATA DALAM BIMBINGAN PESERTA DIDIK DI SEKOLAH DASAR MEBUNG - Saron Lalangpuling; Welmince Onbila, Siria Kamutlaka, Yessy Mata, Petrus Mau Tellu Dony, Halena Muna Bekata (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
Data Is A Crucial Element In The Implementation Of Guidance Services In Elementary Schools Because It Plays A Role In Helping Teachers And Counselors Understand Students' Conditions And Needs Comprehensively. This Article Aims To Explain The Benefits Of Using Data In Student Guidance, The Types Of Relevant Data, And Commonly Used Data Collection Techniques, Both Through Testing And Non-Testing Methods. Information Was Obtained Through An Interview With An Elementary School Teacher SD GMIT 27 mebung Who Plays An Active Role In Guidance Implementation. The Interview Results Indicate That Data Helps In The Process Of Problem Identification, Intervention Planning, And More Accurate And Comprehensive Decision-Making. Data Types Include Personal, Academic, Socio-Emotional, And Physical Development Data. Data Collection Techniques Involve Testing Approaches (Such As Aptitude And Interest Tests) And Non-Testing Approaches (Such As Observation And Interviews). In Conclusion, Optimal Data Utilization Is Crucial To Supporting The Success Of Guidance Services At The Elementary School Level.